Tiny CSS projects - Dowden, Martine; Gearon, Michael (Manning, 2023)
Don't settle for boring web pages! With Cascading Style Sheets you can control color, layout, and typography to make your sites both functional and beautiful. CSS is a essential skill for web developers and designers. This book will help you get started the right way. Tiny CSS projects builds your CSS skills by guiding you through 12 creative mini-projects. Each interesting challenge starts with a downloadable HTML skeleton. As you flesh it out with your own design ideas, you'll master CSS concepts like transitions, layouts, and styling forms, and explore powerful features including Flexbox and Grid. All the skills you'll learn are easy to transfer to full-size applications. When you finish, you'll have an exciting portfolio of designs ready to go for your next project